A unique experiment in undergraduate education in psychoanalysis: The Colorado College class at the Chicago Psychoanalytic Institute. (16th August 2022) - Riker, John H.; Dobson, Marcia D.‐S.
Abstract: In this paper we describe how we created an undergraduate course in psychoanalysis for Colorado College students at the Chicago Psychoanalytic Institute, how the course is constructed in terms of meeting with psychoanalysts, how we create an optimal ambiance for the course, how it is part of a psychoanalysis minor, and why it has been so meaningful for the students. We also articulate why we think teaching psychoanalysis to undergraduates is extraordinarily important and the difficulties and risks in doing so.